Semiotic Analysis of Kaonashi's Character Transformation in the Movie Spirited Away by Hayao Miyazaki - Difitrian, Dinan; Saleh, Sukmawati (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This research aims to analyze the symbolism of Kaonashi's character in the animated film